Xenbase: deep integration of GEO & SRA RNA-seq and ChIP-seq data in a model organism database. Issue Volume 48:Issue D1(2020) (16th November 2019) - Fortriede, Joshua D; Pells, Troy J; Chu, Stanley; Chaturvedi, Praneet; Wang, DongZhuo; Fisher, Malcom E; James-Zorn, Christina; Wang, Ying; Nenni, Mardi J; Burns, Kevin A; Lotay, Vaneet S; Ponferrada, Virgilio G; et al.
Abstract: Xenbase (www.xenbase.org ) is a knowledge base for researchers and biomedical scientists that employ the amphibian Xenopus as a model organism in biomedical research to gain a deeper understanding of developmental and disease processes. Through expert curation and automated data provisioning from various sources Xenbase strives to integrate the body of knowledge on Xenopus genomics and biology together with the visualization of biologically significant interactions. Most current studies utilize next generation sequencing (NGS) but until now the results of different experiments were difficult to compare and not integrated with other Xenbase content. Xenbase has developed a suite of tools, interfaces and data processing pipelines that transforms NCBI Gene Expression Omnibus (GEO) NGS content into deeply integrated gene expression and chromatin data, mapping all aligned reads to the most recent genome builds. This content can be queried and visualized via multiple tools and also provides the basis for future automated 'gene expression as a phenotype' and gene regulatory network analyses.